2012
DOI: 10.1590/s0103-21002012000300019
|View full text |Cite
|
Sign up to set email alerts
|

The clinical seminar as a learning methodology: an evaluation of nursing students' views

Abstract: Objective: To explore students' assessments of the clinical seminar as a complementary teaching method to the clinical practicum experience. Methods: This was a qualitative study based on the hermeneutic phenomenology of Gadamer.Twenty-three open-ended interviews were conducted from among the 132 first-year students who attended an initial clinical practicum. We performed a qualitative analysis of the data using ATLAS.ti software. Results: The students agreed that the clinical seminar gave them the opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Some studies (e.g. Granero-Molina et al, 2012;Hofsten et al, 2010) from contemporary and more mature disciplines have also supported the reasons of why such seminars are or should be conducted. For example, exploring the experience of clinical practices, Granero-Molina et al (2012) revealed that seminars help student gain significant learning from their fellow students and minimise the theory-practice gap.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some studies (e.g. Granero-Molina et al, 2012;Hofsten et al, 2010) from contemporary and more mature disciplines have also supported the reasons of why such seminars are or should be conducted. For example, exploring the experience of clinical practices, Granero-Molina et al (2012) revealed that seminars help student gain significant learning from their fellow students and minimise the theory-practice gap.…”
Section: Discussionmentioning
confidence: 95%
“…A handful of studies (e.g. Alderson et al, 2002;Davies, 2014;Granero-Molina et al, 2012;Hofsten et al, 2010;Zsohar and Smith, 2010) have also explored seminars in the specific context of nursing. For example, Davies (2014) examined the efficacy of using mobile technology (such as Apple iPad) more formally in facilitating enhanced levels of interaction and group cohesion within a series of tutorial sessions involving undergraduate nursing students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to training nurses, the guidelines mean a commitment to new technologies, motivation and active participation from the students, theory-practice integration [3], distance learning [4] and simulation [5]. The incorporation of simulation exercises into nursing programs can provide many students with opportunities helping to improve learning outcomes.…”
mentioning
confidence: 99%
“…Students who prepare using simulations in the laboratory prior to carrying out clinical internships have a better understanding of their learning experience, clearly improving their response when later faced with any type of event in real life. In this sense, it is sometimes the students themselves who demand better theory-practice training, something which both professors and clinical tutors have considerable difficulties to provide [3].…”
mentioning
confidence: 99%